Glycolysis is important for optimal asexual growth and formation of mature tissue cysts by Toxoplasma gondii - Shukla, Anurag; Olszewski, Kellen L.; Llinas, Manuel; Rommereim, Leah M.; Fox, Barbara A.; Bzik, David J.; Xia, Dong; Wastling, Jonathan; Beiting, Daniel; Roos, David S.; Shanmugam, Dhanasekaran (International Journal for Parasitology, 2018)
Toxoplasma gondii can grow and replicate using either glucose or glutamine as the major carbon source. Here, we have studied the essentiality of glycolysis in the tachyzoite and bradyzoite stages of T. gondii, using transgenic parasites that lack a functional hexokinase gene (Delta hk) in RH (Type-1) and Prugniaud (Type-II) strain parasites. Tachyzoite stage 411k parasites exhibit a fitness defect similar to that reported previously for the major glucose transporter mutant, and remain virulent in mice. However, although Prugniaud strain Delta hk tachyzoites were capable of transforming into bradyzoites in vitro, they were severely compromised in their ability to make mature bradyzoite cysts in the brain tissue of mice. Isotopic labelling studies reveal that glucose-deprived tacyzoites utilise glutamine to replenish glycolytic and pentose phosphate pathway intermediates via gluconeogenesis. Interestingly, while glutaminedeprived intracellular Delta hk tachyzoites continued to replicate, extracellular parasites were unable to efficiently invade host cells. Further, studies on mutant tachyzoites lacking a functional phosphoenolpyruvate carboxykinase (Delta pepck1) revealed that glutaminolysis is the sole source of gluconeogenic flux in glucose-deprived parasites. In addition, glutaminolysis is essential for sustaining oxidative phosphorylation in zihk parasites, while wild type (wt) and Delta pepck1 parasites can obtain ATP from either glycolysis or oxidative phosphorylation. This study provides insights into the role of nutrient metabolism during asexual propagation and development of T. gondii, and validates the versatile nature of central carbon and energy metabolism in this parasite. (C) 2018 Australian Society for Parasitology. Published by Elsevier Ltd. All rights reserved.